The Clinical Features of Cystic Parathyroid Adenoma in Chinese Population: A Single-Center Experience - Ya Hu; Ming Cui; Yu Xia; Zhe Su; Xiang Zhang; Quan Liao; Yuxin Jiang; Yupei Zhao (International Journal of Endocrinology)
Objective. Cystic parathyroid adenoma is a rare cause of primary hyperparathyroidism, but its preoperative diagnosis and management remain inconclusive. Method. We retrospectively identified patients with cystic parathyroid adenomas who underwent surgery at Peking Union Medical College Hospital. Results. Patients with cystic parathyroid adenomas had higher serum intact parathyroid hormone and calcium levels, larger maximum tumor diameter, and lower serum inorganic phosphorus level than did those with solid adenomas. Patients with cystic adenomas were predominantly male, and hypercalcemic crisis and atypical adenomas were common. The accuracy of preoperative localization methodologies was lower in patients with cystic adenomas than in patients with solid adenomas. US-guided fine-needle aspiration was performed in 11 patients. In all patients, the iPTH level in cystic fluid was much higher than that in serum. No sign of recurrence was observed after a median follow-up of 39 months. Conclusions. Cystic parathyroid adenomas may not be as rare as previously reported. FNA may be a safe and feasible localization methodology for patients with inconclusive preoperative localization methodologies. Close follow-up is necessary for patients with cystic parathyroid adenomas, which account for a substantial proportion of atypical adenoma cases.